KAJIAN PEMBERIAN PUPUK KANDANG KAMBING DAN PUPUK NPK PHONSKA TERHADAP PERTUMBUHAN DAN HASIL KENTANG HITAM (Plectranthus rotundifolius) - Dayi Laksamana; Dewi Ratna Nurhayati; Efi Nikmatu Sholihah (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2025)
This study aimed to evaluate the effects of goat manure and NPK Phonska fertilizer on the growth and yield of black potato (Plectranthus rotundifolius). Black potato has potential as an alternative food source, but its productivity remains low due to limited cultivation information and the intensive use of chemical fertilizers. The experiment was arranged in a Completely Randomized Design (CRD) with two factors in a 4 × 4 factorial scheme: goat manure (0, 10, 15, and 20 tons/ha) and NPK Phonska (0, 400, 600, and 800 kg/ha), resulting in 16 treatment combinations with three replications (48 experimental plants). Data were analyzed using ANOVA and continued with the Least Significant Difference (LSD) test at the 5% level. The results showed a significant interaction between goat manure and NPK Phonska on tuber diameter, with the best result obtained from 15 tons/ha of goat manure combined with 600 kg/ha of NPK Phonska, producing a tuber diameter of 51.07 mm, significantly higher than the control. Goat manure at 20 tons/ha increased leaf number, flower number, tuber number, tuber length, and tuber weight, while 15 tons/ha was more optimal for tuber diameter and weight. NPK Phonska at 800 kg/ha enhanced plant height, leaf number, and flower number, whereas 600 kg/ha improved tuber diameter and length. This result confirms that the combination of goat manure and NPK Phonska can optimize the growth and yield of black potato. Keywords: Black Potato; Goat Manure; NPK Phonska.